2010
DOI: 10.1063/1.3490675
|View full text |Cite
|
Sign up to set email alerts
|

Production of hollow hemisphere shells by pure Kirkendall porosity formation in Au/Ag system

Abstract: Interdiffusion has been studied in Ag/Au hemispherical core-shell structures on sapphire substrate. In isothermal heat treatments first a relatively fast growth of nanovoids was observed, which was followed by a slower shrinkage process. The void formation is interpreted by pure Kirkendall-porosity formation since Ag-50%Au solid solution has been formed in the shell. In contrary, in all previous publications on hollow nanoshell formation a chemical reaction took place and the shell consisted of the reaction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 23 publications
(24 reference statements)
0
13
1
7
Order By: Relevance
“…An example of the results obtained using this approach is the growth of a void in a rod [72,73,74,75]. The above equations were solved using a central difference scheme in space and an implicit time scheme (see Appendix G).…”
Section: Kirkendall Void Growth With Localized Vacancy Sourcesmentioning
confidence: 99%
“…An example of the results obtained using this approach is the growth of a void in a rod [72,73,74,75]. The above equations were solved using a central difference scheme in space and an implicit time scheme (see Appendix G).…”
Section: Kirkendall Void Growth With Localized Vacancy Sourcesmentioning
confidence: 99%
“…In this same study, the authors show that a similar effect occurs during oxidation or selenization of Co nanocrystals. Since this first report, the nanoscale Kirkendall effect has become very popular and been adopted by many research groups for the synthesis of hollow nanoparticles covering a wide range of materials including sulfides [8,[26][27][28][29][30], oxides [9][10][11], selenides [30,42,53], telurides [14,30], fluorides [53,54], phosphides [17,55] and metals [56][57][58][59]. Through these studies, two conversion mechanisms were identified: symmetrical and asymmetrical.…”
Section: Hollow Nanospheres First Observation: Symmetrical Conversionmentioning
confidence: 99%
“…Отметим, что целью моделирования являлось исследование лишь общих качественных закономерностей для понимания природы процесса и проверки теоретических моделей. Тем не менее, некоторые из наших модельных результатов стали причиной и стимулом для постановки эксперимента группой Беке [51,52] (см. п.…”
Section: атомистическое моделирование эволюции пустотелых нанооболочекunclassified
“…Идея «единого жизненного цикла» нанооболочки с переходом через точку кроссовера, возникшая в процессе теоретических исследований, была экспериментально реализована для бинарной металлической системы Ag/Au и Ag/Pd [51,52].…”
Section: формирование оболочки бинарного раствораunclassified
See 1 more Smart Citation